(untitled) (Asian Journal of Current Engineering and Maths, 2013)
Though telemedicine, a technology used in the health sector to provide healthcare over a distance, has been introduced in Ghana, it has not come to be an integral part of the healthcare services in this country. A telemedicine web application is being designed to enhance healthcare delivery in Ghana. This paper reviewsthe nature of this countryâ€™s healthcare system. The current system and proposed telemedicine web application are also discussed in this paper.Â Keywordsâ€” Telemedicine, system, video, health, communication, Ghana.